Bridging Gaps in Chemistry Instruction: Analyzing the Need for Interactive Learning Media at Senior High School in Sungai Pinang District - Ambar Sari; Farhan Yadi; Fakhili Gulo (AL-ISHLAH: Jurnal Pendidikan, 2025)
The integration of interactive web-based learning media is essential to address challenges in teaching hydrocarbon materials at SMAN 1 Sungai Pinang. Traditional teaching methods, while effective, often lack student engagement, motivation, and interactivity. This study explores the need for digital learning tools to enhance chemistry education. A needs analysis was conducted through surveys and questionnaires to assess student and teacher perceptions regarding existing teaching methods. The validity and reliability of the questionnaire were confirmed to ensure accurate data collection. The study also examined school facilities and academic challenges that impact the implementation of interactive learning. Findings indicate that well-equipped school facilities support the adoption of interactive and digital learning strategies. While traditional methods remain beneficial, a blended learning approach is necessary to optimize student engagement and academic performance. The study also highlights various academic and non-academic challenges faced by students, necessitating further support and development. Regular evaluation of teaching strategies is crucial to adapting to students' evolving needs. The study underscores the importance of interactive web-based learning media in improving teaching effectiveness and student engagement. The findings suggest that supplementing traditional methods with digital tools can enhance comprehension and motivation. This study supports the development of interactive digital learning media to complement traditional chemistry instruction. Implementing blended learning strategies can address current educational challenges, fostering a more engaging and effective learning environment.